Nitrogen Dioxide, Greenhouse Gas Emissions and Transportation in Urban Areas: Lessons From the Covid-19 Pandemic - Restrepo, Carlos E. (Frontiers in Environmental Science, 2021)
Nitrogen dioxide (NO2) is a pollutant of concern in urban areas around the world. The main sources in urban environments are related to the burning of fuel and include transportation, electricity generation, and industrial and residential activities. From a public health perspective NO2 has also been widely associated with respiratory disease, including asthma exacerbation. NO2 also plays a key role in ground-level concentrations of ozone (O3), which is also a public health concern. This policy brief explores the relationships between transportation, climate change mitigation and ambient levels of air pollutants such as NO2. The Covid-19 pandemic has offered a glimpse of how rapid changes in transportation use can result in significant decreases in NO2 concentrations. Data from New York City supports this relationship. Transportation policies aimed at reducing traffic offer an opportunity to both mitigate greenhouse gas emissions and improve air quality. The implementation of measures to rethink public space and the use of streets in response to Covid-19 also provides insights into an additional policy alternative to achieve these goals.